Clinical management of autoimmune hepatitis. Issue 9 (November 2019) - Pape, Simon; Schramm, Christoph; Gevers, Tom JG
Autoimmune hepatitis is a rare and chronic liver disease that is characterised by increased serum transaminases and immunoglobulin G, inflammatory liver histology and presence of circulating autoantibodies. An autoimmune hepatitis diagnosis justifies life-long treatment in most patients in order to prevent development of cirrhosis and end-stage liver disease. The cornerstone of treatment is steroid induction therapy followed by maintenance therapy with azathioprine, which is effective in most cases. For patients who do not respond to standard treatment, second-line treatment with other immunosuppressants can be effective. Treatment should be aimed at biochemical remission of the disease, which is defined as normalization of transaminases and immunoglobulin G. Patients should be monitored intensively during the first months of treatment in order to monitor side-effects, assess symptoms and individualise treatment. Specialist consultation should be sought in difficult-to-treat patients. Future studies and networking initiatives should result in optimization of current treatment strategies in autoimmune hepatitis.